STRATEGY FOR INCREASING FOREIGN EXCHANGE INCOME IN THE TOURISM SECTOR IN CENTRAL ACEH USING THE COMPETITIVE DESTINATION OF HALAL TOURISM MODEL DURING THE COVID-19 PANDEMIC - Likdanawati, Likdanawati; Nur Ilham, Rico; Rahmaniar, Rahmaniar; Fransiska Aulia, Egha; Lisa Nurmaya, Cut (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The impact of the Corona Virus (Covid-19) outbreak on the tourism industry, especially Indonesia, is certainly very influential. A number of cancellations of foreign and domestic tourist arrivals have occurred since the virus outbreak was announced. The plane seats are empty, as well as hotels, cruise operators, and other business potentials. Minister of Tourism and Creative Economy Sandiaga Uno assessed that the limited mobility of the community due to the Covid-19 pandemic and the closure of recreational and entertainment places had a considerable economic impact on the tourism sector. This study aims to formulate a strategy to improve the tourism sector in Indonesia which is declining amid the covid-19 pandemic with the incentive sales method in collaboration with airlines or foreign agents who bring foreign tourists to Indonesia with a specific purpose. will be given a subsidy depending on the number and duration of tourists visiting Indonesia. Through a strategy mechanism to reduce connectivity costs and a competitive destination model (CDM) to anticipate a decline in tourism performance. This scientific research also aims to provide recommendations for sustainable strategies for the Indonesian tourism sector, especially in the province of Aceh in running the tourism sector amid the Covid-19 pandemic. This type of research is a qualitative research using a mix method by conducting interviews with the target population, namely 100 business actors who play a role in driving the economy in the tourism object business in Aceh province and formulating a model for increasing the productivity of the tourism sector by introducing direct promotion methods and collaborating with the government in the process. development and improvement of the tourism sector. In this study, a focus group discussion will be held by inviting local officials from the Aceh provincial tourism office and academics to provide input in completing the model for developing a strategy for increasing tourism productivity by focusing on the incentive sales method. The output of this research is the publication of reputable international journals